Use of volunteers in early years interventions for parents: A scoping review of roles and the extent of evaluation research in this area. - Louise Padgett; Sarah L Blower; Hollie Henderson; Maria Bryant (PLoS ONE)
Early years interventions, particularly those supporting parents in the first 1001 days of their infants life, support healthy development of infants and prevent adverse experiences that can have long term negative impacts. Volunteers are often used to deliver such interventions. This scoping review aimed to explore the roles and characteristics of volunteers across early years interventions and map the evaluation in this field to identify gaps in the literature. A scoping review was conducted according to the Arksey and O'Malley Framework. Academic databases and grey literature sources were searched to identify literature evaluating volunteer-based interventions for parents in the first 1001 days of their infant's life (conception to aged two). Research conducted in the UK or comparable high-income countries since the year 2000 were identified and data relating to the volunteer role, intervention design and evaluation methods were mapped. Sixty-six articles were eligible for inclusion in the review. Volunteers were commonly involved in interventions to provide peer support for a range of parenting related matters, support breastfeeding and the mental and emotional wellbeing of parents. Volunteer roles were categorised based on their background (peers or non-peer volunteers), their responsibilities (provider of peer support, educator or providers of practical support) and the delivery style of their role (in person one to one support, group leader or remote support). Research most often involved exploring the experiences of those involved in receiving or delivering the interventions and measuring outcomes in relation to breastfeeding and parent mental wellbeing. Volunteers play a large role in the provision of early years interventions. Their varied contribution is presented through a typology that will allow comparisons of roles in future research. Further research exploring the impact on the volunteers and the organisation will support decision making around choosing a volunteer led model within early years services.